Clinical characteristics and early prediction of mortality risk in patients with acute organophosphate poisoning-induced shock - Xu, Bing; Zeng, Weijia; Chen, Feng; Lin, Gui; Wang, Mengjie; Ding, Jie; Hong, Ye; Ke, Jun; Wang, Xiaoping; Shang, Xiuling (Frontiers in Medicine, 2023)
Objective: To further get insights of clinical characteristics of acute organophosphate poisoning-induced shock, investigate the relationship between shock and prognosis, and screen risk indicators for prognosis. Methods: A total of 73 patients with acute organophosphate poisoning admitted to our hospital between January 2014 and December 2021 were enrolled in this retrospective study. Patients were divided into the shock group and the non-shock group. The pH value of blood, arterial blood carbon dioxide partial pressure (PaCO2), arterial partial pressure of oxygen (PaO2), base excess (BE), lactic acid (Lac), serum albumin (ALB), total bilirubin (TBIL), alanine aminotransferase (ALT), serum creatinine (Cr), serum potassium (K), serum calcium (Ca), serum sodium (Na) ), blood chloride (Cl), serum troponin I (cTNI), brain natriuretic peptide (BNP), white blood cell count (WBC), hemoglobin (HGB), platelet count (PLT) and other clinical indicators of patients were recorded. Incidence of shock, time of shock onset, and outcomes of patients were also recorded. Cox proportional hazards regression models were performed for analysis. Results: The incidence of organophosphate poisoning-induced shock was 30.1% (22/73), and 72.7% of shock patients developed shock blood pressure within 6 hours. The levels of blood lactate, ALT, Cr, cTNI, BNP and Cl in the shock group were significantly higher than those in the non-shock group, while the level of Ca and pH value was significantly lower than that in the non-shock group (all p<0.05). Moreover, compared with patients without shock (2.0%), the mortality rate was significantly increased in patients with shock (36.4%), which was supported by the results from adjusted Cox proportional hazards regression model. We found that shock and elevated serum creatinine were associated with increased risk of death in patients with organophosphate poisoning (shock: HR, 10.9; 95% CI 1.2-96.3; elevated serum creatinine: HR, 1.0, 95% CI 1.0-1.0). Conclusion:This study indicated the association between elevated serum creatinine and increased mortality rates in patients with organophosphate poisoning, highlighting the importance of the comprehensive management of shock, especially the control of renal function, in these poisoning patients.